(untitled) (British Journal of Global Ecology and Sustainable Development, 2026)
This article examines the specific properties of complex physical systems (CPS), the stages of their systematic analysis, and methods for modeling medical oath biological processes. The study analyzes the effectiveness of modern mathematical tools such as stochastic differential equations, artificial neural networks, and Fourier-Haar series